Lived Experiences of Korean Young Adults After Heart Transplantation: A Phenomenological Approach - Hye Jin Yoo; Eunyoung E. Suh (Elsevier, 2021)
Purpose: This study aimed to explore and describe the lived experience of young adult heart transplant recipients in Korea. Methods: Fifteen young adult heart transplant recipients participated in this qualitative study. Data were collected from March to August 2019 through in-depth individual interviews and analyzed using Colaizzi's phenomenological method. Results: Their experiences about the arduous journey of heart transplant surgery and life after surgery were captured in four themes: (1) unwelcome rebirth without vitality, (2) facing unreachable ordinary tasks in life, (3) lifestyle bordering between burdensome and self-valued, and (4) finding the true meaning of a newly given life. Conclusion: Young adult heart transplant recipients struggled with the burdens of their health problems, which impacted their employment and relationships. The participants' lifelong challenges and psychological turbulence identified in this study provide guidance for health-care providers to understand this population.